2012
DOI: 10.1158/0008-5472.can-11-2602
|View full text |Cite
|
Sign up to set email alerts
|

PTP1B Is an Androgen Receptor–Regulated Phosphatase That Promotes the Progression of Prostate Cancer

Abstract: The androgen receptor (AR)-signaling axis plays a key role in the pathogenesis of prostate cancer. The identification of AR targets contributing to prostate tumorigenesis is thus critical for the development of more effective therapies. Herein, we examined whether the AR could regulate classical protein tyrosine phosphatases, a family of enzymes increasingly associated with oncogenic processes. We found that protein tyrosine phosphatase 1B (PTP1B), a well-established regulator of metabolic signaling, was induc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 47 publications
3
56
0
Order By: Relevance
“…The effect of this has been shown recently in genome wide investigations where AR binding to DNA has been found to be associated with increased accessibility of the location and this could be how AR regulates Ptpn1 expression (29). Others have recently found that AR binds Ptpn1 in human prostate cancer cells, leading to Ptpn1 expression, although the binding was at a different location from the one we found (30). Although these observations implicate AR-mediated expression of Ptpn1, the question remains of why androgen regulates Ptpn1.…”
Section: Discussionsupporting
confidence: 59%
“…The effect of this has been shown recently in genome wide investigations where AR binding to DNA has been found to be associated with increased accessibility of the location and this could be how AR regulates Ptpn1 expression (29). Others have recently found that AR binds Ptpn1 in human prostate cancer cells, leading to Ptpn1 expression, although the binding was at a different location from the one we found (30). Although these observations implicate AR-mediated expression of Ptpn1, the question remains of why androgen regulates Ptpn1.…”
Section: Discussionsupporting
confidence: 59%
“…PTPN1 is frequently amplified in metastatic tumors and high risk primary tumors (47). Downregulation of PTPN1 correlates with better prognosis by delaying tumor occurrence, decreasing tumor growth rates and inhibiting cell migration (41). The predictive signature included two other proteins, LPP and SFXN3, which to our knowledge were not previously associated with prostate cancer.…”
Section: Plasma Biomarkers Identification and Quantificationmentioning
confidence: 84%
“…7C). PTPN1 (protein tyrosine phosphatase nonreceptor type 1) was previously found to be correlated with prostate cancer progression (41); LPP (LIM protein) is involved in cell adhesion; SFXN3 (sideroflexin-3) was previously suggested as a serum tumor marker for oral squamous cell carcinoma (42). Altogether, using PROMISQuan we were able to capture significant differences between healthy and prostate cancer plasma microparticle proteins and identified candidate markers of the disease.…”
Section: Plasma Biomarkers Identification and Quantificationmentioning
confidence: 93%
“…PTP1B was shown to promote cell adhesion and motility in fibroblasts, 17,18 neurons, 3,19 platelets, 4 and several tumor cell lines. 12,[20][21][22] An inhibitory role has been described in fibroblasts, 23,24 primary aortic smooth muscle cells, 25 ovarian cancer cells, 26 and in glioblastoma multiforme tumor cell invasion in mice. 27 Remarkably, the positive role of PTP1B in cell motility was frequently associated with the stimulation of integrin-dependent signaling.…”
Section: Long-range Impact Of Ptp1b On Cell Adhesion and Motilitymentioning
confidence: 99%